The Practice of Professional Learning Community in Trust Schools, Transformation Schools and High Performing Schools in Selangor Malaysia - Ramlan Mustapha, Siti Nafsiah Ismail, Zuraidah Abdullah (International Journal of Advanced Science and Technology, 2019)
This study aims to identify the level of Professional Learning Community (PLC) in 3 different types of school namely in Selangor. A total of 450 Malay language teachers from 42 schools in Selangor were involved as respondents in this study. This quantitative study uses survey methods for the purpose of data collection. Data were collected through a set of questionnaires which was developed through Fuzzy Delphi method based on the consensus of 12 experts. The quantitative data collected were analyzed using SPSS version 23.0 and SEM PLS 3.0. This study conveys the level of PLC practice of Malay language teachers in Selangor and the outcome is high for each PLC dimension through overall average score (Min = 3.92, SP = 0.509). In addition, the findings also show that there is a substantial relationship across dimensions of PLC. Finally, it is hoped that the findings of this study will have a positive impact on the implementation of PLC in Malaysian schools as well as for the improvement of student learning outcome.